The effect of anaerobic power on short distance swimming performance in prepubertal male swimmers - Aydın Şentürk; Maya Budak (Turkish Journal of Kinesiology, 2023)
This relational model study aimed to assess the anaerobic power and short distance swimming performance in prepubertal male swimmers. A total of 20 male swimmers, age mean = 11.40±1.39 yrs, participated in this study. All participants trained on approximately two hours per session, five times per week. A mat was used to collect data on vertical jump. Swimming performance was evaluated for 50 meters in swimming pool using a stopwatch. The arm Wingate was used to assess the anaerobic arm power of the participants. It was observed that the peak power obtained from the vertical jump explained the swimming performance by 21.7%. On the other hand, when the effect of the anaerobic peak power obtained from the arm Wingate on the swimming performance of the swimming children was examined, it was seen that the peak power of the arm explained the swimming performance by 26.8%. In conclusion, it is seen that the anaerobic power obtained from the arms and legs affects the short-distance swimming performance by approximately 50%. It can be said that the power produced from the arm is more important by 5%. For 50 meters swimming performance, it is recommended that trainers include exercises to increase arm strength.